Successful Treatment of Bullous Pemphigoid Lesions by Berberine Stamp Therapy: A Case Report and Literature Review - Cheng, Linyan; Wang, Yi; Lu, Hanzhi; Guo, Wanjun; Yan, Ge; Zhu, Jianyong; Guo, Dongjie; Li, Fulun (Frontiers in Medicine, 2022)
Bullous pemphigoid (BP) is a life-threatening autoimmune disease of the skin that is mainly characterized by a large range of tension blisters and intense itching of the skin. The 1-year mortality rate of BP was 23.5%. Superinfection caused by skin lesion ulceration is one of the important causes of disease death. Therefore, it is challenging to control infection and improve skin wound healing. Here, we report the case of an elderly woman who presented with BP and involved the oral mucosa. The patient was successfully treated with hormones combined with topical berberine, and 95% of the patients’ lesions healed completely after 1 month. In addition, we inductively analyzed the current treatments for BP to provide a reference for BP clinical treatment.